Hematite facet-mediated microbial dissimilatory iron reduction and production of reactive oxygen species during aerobic oxidation. (1st May 2021) - Han, Ruixia; Lv, Jitao; Zhang, Suhuan; Zhang, Shuzhen
Highlights: Hematite surface influences microbial iron reduction and aerobic oxidation cycles. {001} facets have a higher Fe(III) reduction efficiency than {100} facets. {100} facets display a higher ability to produce ROS than {001} facets. Accessibility of electron donors to surface iron atom determines Fe(III) reduction. Activation energy barrier for O2 reduction by surface Fe dominates ROS production. Abstract: Microbial dissimilatory iron reduction and aerobic oxidation affect the biogeochemical cycles of many elements. Although the processes have been widely studied, the underlying mechanisms, and especially how the surface structures of iron oxides affect these redox processes, are poorly understood. Therefore, {001} facet-dominated hematite nanoplates (HNP) and {100} facet-dominated hematite nanorods (HNR) were used to explore the effects of surface structure on the microbial dissimilatory iron reduction and aerobic oxidation processes. During the reduction stage, the production of total Fe(II) normalized by specific surface area (SSA) was higher for HNP than HNR due to steric effects and the ligand-bound conformation of the connection between iron on different exposed facets and electron donors from microorganisms. However, during the aerobic oxidation stage, both the SSA- and Fe(II)-normalized reactive oxygen species (ROS), including hydrogen peroxide (H2 O2 ) and hydroxyl radical (OH), were higher for HNR than HNP. Theoretical calculation results showed that the {100} facets exhibited a lower activation energy barrier for oxygen reduction reaction than {001} facets, supporting the experimental observation that {100} facet-dominated HNR had a higher ROS production efficiency than {001} facet-dominated HNP. These results indicated that surface characteristics not only mediated the microbial reduction of Fe(III) but also affected the aerobic oxidation of microbially reduced Fe(II). Accessibility of electron donors to surface iron atom determined the reduction of Fe(III), and activation energy barrier for oxygen reduction by surface Fe(II) dominated the ROS production during the redox processes. This study advances our understanding of the mechanisms through which ROS are produced by iron (oxyhydr)oxides during microbial dissimilatory iron reduction and aerobic oxidation processes. Graphical abstracts: Image, graphical abstract